Who Is This God of Whom You Speak? Counseling Students' Concept of God. Issue 2 (October 2016) - Cashwell, Craig S.; Young, J. Scott; Tangen, Jodi L.; Pope, Amber L.; Wagener, Alwin; Sylvestro, Hallie; Henson, Robert A.
Abstract : Many clients bring a belief in God or a Higher Power into counseling sessions. What is less clear, however, is how counselors conceptualize "god, " which may affect how spirituality is integrated in the counseling process. To explore this question, the authors conducted a concept map study of god images among counseling students. Results suggest that students harbor broad and diverse conceptualizations of god, which may affect the counseling process.